Core-log integration - Lovell, M. A., 1955-; Harvey, P. K. (Geological Society special publication, 1998)
This volume addresses some of the problems of core-log integration encountered by scientists and engineers from both industry and academia. Core and log measurements provide crucial information about subsurface formations. Their usage, either for integration or calibration, is complicated by the different measurement methods employed, different volumes of formation analysed and, in turn, the heterogeneity of the formations. While the problems of comparing core and log data are only too well known, the way in which these data can be most efficiently combined is not at all clear in most cases. In recent years there has been increased interest in this problem, both in industry and academia, due to developments in technology which offer access to new types of information and, in the case of industry, pressure for improved reservoir models and hydrocarbon recovery. The application of new numerical methods for analysing and modelling core and log data, the availability of core scanning facilities, and novel core measurements in both two and three dimensions, currently provide a framework for the development of new and exciting approaches to core-log integration. The contributions within Core-Log Integration geologically range from hydrocarbon-bearing sediments in the North Sea to the volcanic rocks that form the upper part of the oceanic crust.